Understanding Muslim Plurality: Problems of Categorizing Muslims in Postcolonial Indonesia - Muhamad Ali (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
Islam in Indonesia has received significant academic attention. One important finding is the categorization of beliefs and behaviors of Muslims, which proves the plurality of Islam. However, these categorizations—such as santri-abangan-priayi, traditionalist-modernist, political-cultural, fundamentalist-liberal, great tradition-little tradition, and global-local—must be critically approached. The most appropriate categorization is one that is closer to reality. The santri-abangan-priayi categorization developed in the 1960s demonstrates Javanese centrism in the study of Indonesian Islam and shows a static, closed system that should be carefully used to refer to Muslims outside of Java and in the present era. The traditionalist-modernist category actually carries modernization assumptions and therefore should not be viewed statically. The differentiation of political-cultural is also difficult to apply in many cases, such as when an Islamic group is involved in both political and cultural activities simultaneously. Similarly, the terms great tradition-little tradition to refer to Sharia Islam and Sufi Islam are less relevant in cases where specific Islamic groups practice both Sharia and Sufism simultaneously, besides the fact that the terms big and small assume one pattern is more valuable than others religious patterns. The global and local perspectives in understanding the diversity of Islam can avoid overly general labeling, but it is still difficult to determine which aspects are global and which are local and challenging to measure religious change accurately. Even more challenging in understanding the plurality of Islam is how to determine a religious act and what is not religious (secular).